The Analysis of Research Center Establishment Preparation at dr. Kariadi Hospital, Semarang - Retnaningsih Retnaningsih; Anies Retnaningsih; Chriswardani Suryawati (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
Background: A good preparation is required to set up a research center. Management support, planning, infrastructures, human resources, and funding are factors that are closely related to the requirements of the establishment of a research center.Objective: To analyze the preparation of the research center establishment at dr. Kariadi Hospital, Semarang.Method: This study was using analytic descriptive. As many as 180 respondents consisting of : hospital directors, heads of medical staff unit, specialists, general practitioners, paramedics, and interns, were involved in this study. Data collection was done through structured questionnaires. The data analysis including univariate analysis, bivariate analysis using chi-square, and multivariate analysis using logistic regression.Results: Factors that are significantly related to the preparation of the research center establishment are management support (p value 0.005; probability level of 39.66%), infrastructure (p value 0.020; probability level 35.97%), organizational system (p value 0.041; probability level 35.02%). Other factors that are not directly related to the preparation of a research center establishment are research personnel, quality criteria, research startups, achievement progress and constraints.Conclusion: Preparation for the establishment of a research center requires a full support of hospital management, both internal and external support.